Formulasi Dan Aktivitas Antioksidan Sirup Air Kelapa Tua (Cocos nucifera L) Dan Ekstrak Buah Merah (Pandanus conoideus L) Dengan Metode DPPH - Siti Mun Muhliza Ahmad; Ratih Arum Astuti; A.M. Muslihin (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Mature coconut water (Cocos nucifera L.) has the potential as a health drink but is often discarded as waste. Red fruit (Pandanus conoideus L.) is an endemic plant of Papua that is rich in antioxidants. The combination of both is expected to produce a beneficial herbal syrup preparation. Objective: To formulate a combination syrup of mature coconut water and red fruit extract and to determine its antioxidant activity using the DPPH method. Methods: Red fruit extract was obtained by maceration using 96% ethanol. Phytochemical screening was performed on both ingredients. The syrup was prepared with the addition of sugar, citric acid, vanilla, and CMC. Physical evaluation included organoleptic, homogeneity, pH, viscosity, and clarity tests. Antioxidant activity was tested using the DPPH method at a wavelength of 517 nm using a UV-Vis spectrophotometer. Results: Phytochemical screening showed that mature coconut water contains alkaloids, while red fruit extract contains flavonoids, tannins, saponins, and alkaloids. The syrup evaluation met SNI requirements: organoleptic (reddish-orange color, characteristic odor, sweet taste), homogeneous, pH 5–6, viscosity 250 mPa·s, and clear. The IC50 values of the syrup in three consecutive replicates were 550.34 μg/mL, 2282.3 μg/mL, and 2863.4 μg/mL, which are classified as weak antioxidant activity (IC50 > 200 ppm). Conclusion: The combination syrup of mature coconut water and red fruit extract exhibits weak antioxidant activity but meets the physical quality standards of the preparation. This preparation has the potential to be developed as a herbal health drink.